Effect of Fluid Viscosity on Fault Reactivation and Coseismic Weakening. Issue 1 (16th January 2020) - Cornelio, C.; Passelègue, F. X.; Spagnuolo, E.; Di Toro, G.; Violay, M.
Abstract: High‐viscosity fluids are often used during hydraulic fracking operations in georeservoirs. Here we performed dedicated experiments to study the influence of fluid viscosity on fault reactivation and associated induced earthquakes. Experiments were conducted in the rotary‐shear machine Slow to HIgh Velocity Apparatus on experimental fault of Westerly granite saturated by fluids with increasing viscosity (at room temperature) from 0.1 mPa s (water) to 1.2 Pa s (99% glycerol). Fault reactivation was triggered at constant effective normal stress by increasing the shear stress acting on the fault. Our results showed that independent of the viscosity, fault reactivation followed a Coulomb‐failure criterion. Instead, fluid viscosity affected the fault weakening mechanism: flash heating was the dominant weakening mechanism in room humidity and water‐saturated conditions, whereas the presence of more viscous fluids favored the activation of elasto‐hydrodynamic lubrication. Independent of the weakening mechanism, the breakdown work W b dissipated during seismic faulting increased with slip U following a power law ( W b ∝ U 1.25 ) in agreement with seismological estimates of natural and induced earthquakes. Plain Language Summary: One of the most alarming recent findings in solid earth sciences is the worldwide exponential increase of human‐induced seismicity. This is due to engineering operations in deep reservoirs for hydrocarbon production, CO2 storage, wastewater storage, and exploitation of geothermal resources which result in the reactivation of faults hosted in the reservoirs. While the reactivation of faults due to fluid pressure has been extensively studied, the influence of fluid properties including its viscosity has been overlooked, even if the viscosity of injected fluids spans from the one of water to that of honey. In this study, we discuss the influence of stress perturbations on the reactivation of fluid‐permeated experimental faults and on induced earthquakes. Our experimental observations suggest that the viscosity of the fluid does not influence the onset of fault reactivation. Instead, the viscosity of the fluid controls the type of deformation mechanism activated during induced earthquake rupture. Key Points: The viscosity of the injected fluid does not influence the initial strength of experimental faults Fault weakening mechanisms during simulated seismic slip depend on fluid viscosity The magnitude of the breakdown energy is independent of the fault weakening mechanism